Edinburgh 1910 revisited : Give us friends : an Indian prospective on one hundred years of mission - Fox, Frampton F. (Bangalore, India : CMS / ATC, Asian Trading Coproration, 2010)
"A century of mission has occurred since the landmark 1910 International World Mission Conference in Edinburgh, Scotland. This conference is arguably the most significant conference in the history of Christianity" from publisher description.
Spirit and mission in the Bible: the spirit as the agent of divine life-giving communion / Cornelis Bennema -- Salvation-present, future and its link to conversion, baptism, and participation in the sacramental life of the church / Joseph Matam -- Edinburgh 1910 and Christian mission among other faiths / S. Devashayam Ponraj -- Witnessing Christ in the company of Hindus . K. P. Aleaz -- Prospects and challenges that engulf Christian missions in a postmodern context / Santhosh J. Sahayadoss -- Mission and postmodernity, neocolonialism, and globalization / John Arun Kumar -- Papers from the 16th annual Centre for Mission Studies Consultation, UBS, Pune.
Papers from the 16th annual Centre for Mission Studies Consultation, UBS, Pune.
Includes bibliographical references.
Keywords: Edinburgh -- Weltmissionskonferenz (1910); Missions -- Congresses